Translation and psychometric analysis of urdu version of modified polycystic ovary syndrome health related quality of life questionnaire (MPCOSQ-U) - Rabbiya Zaman; Sarah Ehsan; Abeer Fatima; Sumaiyah Obaid; Javeria Shahzadi (BMC, 2024)
Abstract Background Polycystic ovary syndrome is a metabolic disorder prevalent among females of reproductive age. The symptoms of PCOS profoundly affect the quality of life of these females. Outcome measures specific to PCOS are crucial to the management of these patients. The MCPOSQ is a validated tool to measure the health-related quality of life specific to PCOS. The purpose of this study was to translate the modified polycystic ovary syndrome quality of life questionnaire (MPCOSQ) and to determine the reliability and validity of the modified polycystic ovary syndrome quality of life questionnaire Urdu version (MPCOSQ-U). Methodology This cross-sectional study was conducted in Islamabad/Rawalpindi. The MPCOSQ was translated to Urdu and validated by expert gynaecologists. The MPCOSQ-U and SF-36 were administered to one hundred eighty females with PCOS. The MPCOSQ-U was evaluated for internal consistency, test-retest reliability, factor analysis, face validity, content validity and construct validity. Results The average age (years) of the females was 25.27(1.83). The MPCOSQ-U showed excellent test-retest reliability and internal consistency (ICC2,1=0.95, Cronbach's α = 0.97). The content validity index (CVI) was 0.92. There was a statistically significant but weak positive correlation between MPCOSQ-U and SF-36 (r = .186, p = .012). Conclusion The Urdu version of the modified version of the polycystic ovarian syndrome quality of life questionnaire is a validated and reliable tool to assess the quality of life of Pakistani females with PCOS. This is an important step to cover the language barrier, which influences the outcome assessment in PCOS.